Right bundle branch block evolving to myocardial ischemia in a patient with chronic middle back pain: a case report - Meity Ardiana; Inna Maya Sufiyah; Muhammad Nuh Hamdani (Journal of Medical Case Reports, 2023)
Abstract Background A right bundle branch block (RBBB) is rarely found in patients with myocardial infarction (MI). In addition, back pain is an atypical complaint in patients with angina. Case A 77-year-old Javanese male was admitted with middle back pain that he had had for several months but that had become worse in the past week. He received an oral nonsteroidal anti-inflammatory drug as analgesic therapy but the pain did not improve. The patient came to the emergency room and an electrocardiogram (ECG) showed complete RBBB and first-degree atrioventricular block. Three days after hospital admission, his chief complaint of pain had worsened, and ECG showed new deep arrow-head inverted wave at V3–V6, II, III, and aVF, as well as infero-anterolateral ischemia. The coronary angiography revealed 95% critical stenosis in left circumflex artery. Discussion It is a challenge for clinicians to recognize and carefully assess a patient’s complaints even if they are admitted for pain that is “atypical” of MI. When ECG shows changes, clinicians need to pay attention to a tricky, hidden, and life-threatening occlusion of the coronary artery.